Low Complexity Byzantine-Resilient Consensus - Correia, Miguel (2003)
The application of the tolerance paradigm to security intrusion tolerance has been raising a good deal of attention in the dependability and security communities. This paper is concerned with a novel approach to intrusion tolerance. The idea is to use privileged distributed components generically designated by wormholes to support the execution of intrusion-tolerant protocols, often called Byzantine-resilient protocols in the literature. The paper introduces the design of wormhole-aware intrusion-tolerant protocols using a classical distributed systems problem: consensus. The system where the consensus protocol runs is mostly asynchronous and can fail in an arbitrary way, except for the wormhole, which is secure and synchronous. Using the wormhole to execute a few critical steps, the protocol manages to have a low time complexity: in the best case, it runs in a single round, even if some processes are malicious. The protocol is also arguably faster than classical Byzantine protocols, because it does not use public-key cryptography in runtime. The protocol has the interesting feature of not being bound by the FLP impossibility result